Measuring voluntary activation of the Quadriceps femoris during isokinetic concentric contractions - Malloggi, Chiara; Catino, Luigi; Rota, Viviana; Scarano, Stefano; Tesio, Luigi (Isokinetics and exercise science, 2019)
BACKGROUND: It is known that Voluntary Activation (VA) of muscles may be lower during isokinetic concentric (CON) contractions than during isometric (ISOM) contractions, and that it may be further decreased in various motor impairments. OBJECTIVE: The aim of this study was to validate the Interpolated Twitch Technique (ITT) for quantifying VA of the Quadriceps femoris during CON contractions (knee extension at 60 and 120 ∘ /s, CON60 and CON120, respectively). METHODS: Pairs of electrical stimuli were delivered to the Quadriceps femoris of twenty-two healthy subjects at 50 ∘ of knee flexion. Participants were instructed to exert five different levels of effort in decreasing order between 100% and 20% maximal voluntary efforts in ISOM and CON contractions. RESULTS: Through a linear regression model, a significant relationship between measures of VA and moment was observed for all the three contraction conditions: slopes (95% confidence intervals) = 1.04 (0.98–1.11), 0.96 (0.89–1.02) and 0.84 (0.78–0.91); intercepts = - 5.22 ( - 8.61– - 1.83), 4.16 (0.71–7.62) and 14.58 (10.76–18.39), for ISOM, CON60 and CON120 contractions, respectively. This supported the validity of the method. CONCLUSIONS: It is concluded that ITT can be a valid method for measuring VA during CON contractions, potentially useful both in sports and rehabilitation studies.